Alleviation of Intestinal Inflammation by Oral Supplementation With 2-Fucosyllactose in Mice - Grabinger, Thomas; Glaus Garzon, Jesus Francisco; Hausmann, Martin; Geirnaert, Annelies; Lacroix, Christophe; Hennet, Thierry (Frontiers in Microbiology, 2019)
Milk oligosaccharides exert a prebiotic action that contributes to the development of the infant gut microbiota during lactation. Given that milk oligosaccharides remain intact after passage through stomach and small intestine, they can potentially influence the composition of the gut microbiota when ingested as dietary supplements after weaning. To address the regulatory effects of specific oligosaccharides in colitis linked to the microbiota composition, we have supplemented interleukin-10 null (Il10-/-) mice with four major milk oligosaccharides. We found that oral supplementation with 2-fucosyllactose significantly decreased the severity of colitis by promoting the expansion of Ruminococcus gnavus. The anti-inflammatory impact of R. gnavus was confirmed by reconstitution of antibiotic-treated Il10-/- mice and by stimulation of dendritic cells in vitro. This study demonstrates that post-weaning administration of specific milk oligosaccharides can shift the composition of the gut microbiota to lessen chronic inflammation as observed in Il10-/- mice.